ANATOMICAL STRUCTURE OF FEMALE SEX ORGANS IN SHEEP AND THEIR INFLAMMATION - Assistent A. Chorshambiyev; Assistent Sh. Achilov (Scholars Digest Publishing, 2023)
In sheep, the female reproductive organs include the vagina, vagina, clitoris, uterus, and ovaries. These organs are involved in important physiological processes. These organs are located in the pelvic cavity of sheep. Inflammations are common.
Keywords: Endometritis, inflammation, vulvitis, cervicitis, vaginitis, ovaritis, corpus luteum, pathological corpus luteum.